Release of Prisoners During the Covid-19 Pandemic In Perspective of Decree of the Minister of Law and Human Rights Number 10 of 2020: Pembebasan Narapidana Dalam Masa Pandemi Covid-19 Dalam Persepektif Keputusan Menteri Hukum Dan Hak Asasi Manusia Nomor 10 Tahun 2020 - Imam, Syafarul; Phahlevy, Rifqi Ridlo (Universitas Muhammadiyah Sidoarjo, 2021)
This study aims to determine and examine the juridical basis and the process of implementing assimilation during the COVID-19 pandemic. The research method used by the author is normative juridical using a statutory approach or better known as a statute approach and a conceptual approach. The conclusion of this study explains that the Decree of the Minister of Law and Human Rights Number 10 of 2020 is a lex specialist or special rule of Law Number 12 of 1995 which is a lex generalis or general rule where the Decree of the Minister of Law and Human Rights No. 10 of 2020 as lex specialists or special rules only apply to the emergency situation of the covid-19 pandemic on the basis of tackling the prevention of the spread of the covid-19 virus. Decree of the Minister of Law and Human Rights No. 10 of 2020 is a special policy that has positive and negative impacts. The positive impact of this decision is that it can reduce the number of inmates in correctional facilities as a form of preventing the spread of the covid-19 virus, while the negative impact of this decision is that the process of assimilation carried out at home results in the repetition of criminal acts by inmates who received an assimilation program during the COVID-19 pandemic. so that the role of supervisors is expected to work well and maximally to minimize the occurrence of criminal acts again committed by prisoners who receive an assimilation program during the covid 19 pandemic.